Non-Hodgkin lymphoma of bone in an HIV-infected patient from Argentina - Sandkovsky, Uriel; Martin, Pablo Fernando; Bissio, Emiliano (The Journal of Infection in Developing Countries, 2011)
Introduction: Human immunodeficiency virus (HIV)-infected patients are at higher risk for development of Non-Hodgkin's lymphoma (NHL). The estimated incidence of NHL in patients with acquired immunodeficiency syndrome (AIDS) is much higher when compared to the general population. Most AIDS-associated NHL are of intermediate- or high-grade B-cell type and involve extranodal sites more frequently. The most common sites are the central nervous system (CNS), gastrointestinal tract, liver, bone marrow and soft tissues. Methodology: We describe a 42-year-old male with risk factors for HIV infection who presented with left leg pain and an osteolytic lesion of the left medial tibia. He was subsequently diagnosed with HIV disease and an open biopsy of his left tibia established the diagnosis of NHL. Results: After starting antiretroviral therapy followed by chemotherapy he achieved remission. Conclusion: Bone lymphomas account for 3% of malignant bone tumors and 4-7% of all extranodal sites. NHL of bone has been infrequently described in patients with AIDS. To our knowledge, this is the first report of NHL of the bone in Argentina. <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} > <! [endif] > Background: HIV-infected patients are at higher risk for development of Non-Hodgkin’s lymphomas (NHL). The estimated incidence of NHL in patients with the acquired immunodeficiency syndrome (AIDS) is much higher when compared to the general population. Most AIDS associated NHL (AIDS-NHL) are of intermediate or high grade B-Cell type and involve extranodal sites more frequently. The most common sites are central nervous system (CNS), gastrointestinal tract, liver, bone marrow and soft tissues. Methods: We describe a 42 year old male with risk factors for HIV infection who presented with left leg pain and an osteolytic lesion of the left medial tibia; He was subsequently diagnosed with HIV disease and an open biopsy of his left tibia established the diagnosis of NHL. Results: After starting antiretroviral therapy followed by chemotherapy, he achieved remission. Conclusion: Bone lymphomas account for 3% of malignant bone tumors and 4-7% of all extranodal sites. NHL of bone has been infrequently described in patients with AIDS. To our knowledge, this is the first report of NHL of the bone in Argentina.<-->